2021
DOI: 10.3390/molecules26051239
|View full text |Cite
|
Sign up to set email alerts
|

Tiliacora triandra (Colebr.) Diels Leaf Aqueous Extract Inhibits Hepatic Glucose Production in HepG2 Cells and Type 2 Diabetic Rats

Abstract: This study investigated the effects of Tiliacora triandra (Colebr.) Diels aqueous extract (TTE) on hepatic glucose production in hepatocellular carcinoma (HepG2) cells and type 2 diabetic (T2DM) conditions. HepG2 cells were pretreated with TTE and its major constituents found in TTE, epicatechin (EC) and quercetin (QC). The hepatic glucose production was determined. The in vitro data were confirmed in T2DM rats, which were supplemented daily with 1,000 mg/kg body weight (BW) TTE, 30 mg/kg BW metformin or TTE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“… 50 , 51 Weerawatanakorn et al and Pasachan et al identified the presence of a high content of phenolic constituents in T. triandra leaves extract and these compounds were adjudged as the active principles showing antioxidant, anti-inflammatory and antidiabetic effects in their study. 48 , 52 Our UHPLC-DAD-ESI-QTOF-MS analysis of TT extract indicated the presence of phenolic and flavonoids, which may have accounted for the excellent antioxidant and anti-inflammatory effects against CDDP induced neurotoxicity. For instance Liu et al reported that isovitexin protected against CDDP induced renal injury via anti-inflammatory and antioxidative properties.…”
Section: Discussionmentioning
confidence: 95%
“… 50 , 51 Weerawatanakorn et al and Pasachan et al identified the presence of a high content of phenolic constituents in T. triandra leaves extract and these compounds were adjudged as the active principles showing antioxidant, anti-inflammatory and antidiabetic effects in their study. 48 , 52 Our UHPLC-DAD-ESI-QTOF-MS analysis of TT extract indicated the presence of phenolic and flavonoids, which may have accounted for the excellent antioxidant and anti-inflammatory effects against CDDP induced neurotoxicity. For instance Liu et al reported that isovitexin protected against CDDP induced renal injury via anti-inflammatory and antioxidative properties.…”
Section: Discussionmentioning
confidence: 95%
“…They investigated the underlying mechanism and the in vivo effects in a type 2 diabetes mellitus (T2DM) rat model. They asked whether TTE could act as a nutritional agent in the management of T2DM and prevent complications such as non-alcoholic steatohepatitis, non-alcoholic fatty liver disease, and eventual cirrhosis ( Pasachan et al, 2021a ). They used a Diels aqueous extract of TTE to affect glucose synthesis in cells with T2DM and HepG2 cells.…”
Section: Quercetin and Gastrointestinal Cancermentioning
confidence: 99%
“…Similar to metformin, TTE showed antidiabetic, anti-triglyceridemic, anti-hyperglycemic, and antioxidant effects in rats with T2DM. TTE may be used as a nutraceutical agent in individuals with insulin resistance, obesity, or those receiving antidiabetic medication ( Pasachan et al, 2021a ). Table 5 lists some studies on the therapeutic effects of quercetin in HCC.…”
Section: Quercetin and Gastrointestinal Cancermentioning
confidence: 99%
“…T. triandra is used not only as food but also as traditional medicine. For example, it has been reported as an antipyretic, detoxication agent, anti-inflammatory agent [ 20 ], antimalarial agent [ 21 ], antimycobacterial agent [ 22 ], antioxidant [ 23 ], antidiabetic agent [ 24 ], and anticancer agent [ 25 , 26 ]. Several compounds identified in T. triandra include alkaloids [ 25 ], phenolic compounds [ 23 , 27 ], flavonoids, polysaccharides [ 27 ], and fatty acids [ 26 ].…”
Section: Introductionmentioning
confidence: 99%